Regulation of structural and terahertz properties of TiC nanoparticles by carbon-coating and nitrogen-doping. (October 2022) - Huang, Feirong; Fan, Shuting; Tian, Yuqi; Qu, Xinghao; Li, Xiyang; Javid, Muhammad; Zhang, Xuefeng; Zhang, Zhidong; Dong, Xinglong
Abstract: Carbon-coated titanium carbide nanocomposites (TiC@C NCs) were synthesized by arc discharge plasma under an atmosphere of Ar and CH4 gas, and nitrogen-doped carbon-coated titanium carbonitride nanocomposites (Ti(C, N)@NC NCs) were also obtained using a mixture gas of N2 and CH4 . Terahertz (THz) optical and dielectric properties of these nanostructures were investigated using a THz time-domain spectrum system, and the extracted conductivity was analyzed to understand the transport mechanism. The dielectric response in these nanostructures is dominated by ionic polarization with a relaxation behavior, and absorption characteristic is free carrier absorption dependent on conductivity. Ti(C, N)@NC NCs achieve the enhanced dielectric response and high absorption loss due to nitrogen-doping increasing charge disorder and conductivity. AC conductivities of the samples were fitted to the universal power low function and indicated that the transport mechanism is electronic hopping. Highlights: Structural regulation of nanostructures was achieved by arc discharge plasma. Dielectric and optical properties of nanostructures in the THz band were reported. N-doping enhances dielectric response and optical absorption of nanostructures. Carrier transport in nanostructures in the THz band is dominated by electronic hopping.